The Instructional Challenges of Non-Thai Teachers in English Language Education for Thai Primary Students: A Case Study at Selected Thai Schools - Jihan Fadhillah; Abdul Rohim; Muh. Iqbal Firdaus; Sanitpim Thongbab (Universitas Muhammadiyah Jember, 2026)
This study investigates instructional challenges faced by a non-Thai teacher in teaching English to Thai primary students within a cross-cultural classroom context. While previous research has primarily emphasized students’ perceptions of foreign teachers, limited attention has been given to classroom-based instructional processes. This qualitative study involved 12 Thai primary students from Grades 3 to 6. Data were collected through classroom observations, reflective teaching notes, students’ drawings, and short interviews and were analyzed using thematic analysis. The findings indicate that instructional challenges emerged in managing student engagement, delivering comprehensible English input, addressing affective barriers to participation, navigating the absence of Thai language support, and managing cross-cultural novelty in the classroom. These challenges required ongoing instructional adjustment, including the use of visual support, modeling, repetition, and peer assistance to facilitate understanding and participation. The study highlights the complexity of teaching young learners in cross-cultural EFL settings and underscores the importance of adaptive classroom practices in multilingual primary education contexts.